Analysing The Optimisation Of Capital Structure Of Chinese Listed Companies - Tian, Yunlong (2017)
Company managers usually aim to maximise both shareholder value and the value of the firm itself. To achieve these overarching objectives, managers need to employ an optimising capital structure that lowers the costs of capital for the company. However, the firm’s management is also required to understand the determining factors of these financial structures so as to better decide on the optimal capital structure. This paper seeks to analyse the optimisation of the financing decisions of listed Chinese firms, as well as establish the critical factors for an optimal structure. The study’s data was obtained from CSMAR DataStream, and previous studies were utilised for the computation of company-specific features. The research analysed a seven-year period, from 2010 to 2016, utilising data from a total of ninety listed companies, which resulted in eight hundred and seventy-six observations. The results indicated that asset tangibility, profitability, and liquidity are the most critical determining factors of financial structure. The study also found that firms optimise their capital structures, as doing so maximises the firm’s value by reducing the costs associated with either equity or debt capital. The present study therefore recommends that company-specific factors be taken into consideration when making financing decisions